1963
DOI: 10.1071/bi9630099
|View full text |Cite
|
Sign up to set email alerts
|

Environment and Sporulation in Phytopathogenic Fungi V. Monilinia Fruc'ticola (Wint.) Honey: Effect of Water Relations on Regeneration of Conidia in Vivo

Abstract: An investigation into the role of water relations in determining conidial regeneration of Monilinia f1"Ucticola (Wint.) Honey on infected leaves, peduncles, and mummified fruitlets of apricot (Prunus armeniaca L. cv. Trevatt) demonstrated the following points:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…It was noted that the new conidia produced on the surface of these fruit originated from sporodochial cushions formed immediately after infection. Thus, regeneration of conidia occurred from the same sporulating area as reported for M. fructicola (Corbin & Cruickshank, 1963). This indicates a relationship between sporulating structures formed after infection and later (re)sporulation on the same fruit.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…It was noted that the new conidia produced on the surface of these fruit originated from sporodochial cushions formed immediately after infection. Thus, regeneration of conidia occurred from the same sporulating area as reported for M. fructicola (Corbin & Cruickshank, 1963). This indicates a relationship between sporulating structures formed after infection and later (re)sporulation on the same fruit.…”
Section: Discussionsupporting
confidence: 60%
“…Corbin & Cruickshank (1963) showed that apricot fruitlets, collected in the field after a brown rot epidemic caused by M. fructicola , were able to produce several crops of conidia. They showed that with short incubation periods of 12 h at 20°C and 98% RH, fruitlets produced up to 10 crops of conidia before regeneration of conidia ceased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was supported by Corbin's (1962) work on M. fructicola where RH did not affect sporulation intensity on fruits once infection was established. It is well known that overwintered mummified fruits of brown rot need free water to sporulate (Corbin & Cruickshank, 1963; Byrde & Willetts, 1977). Results from the present study suggest that free water on freshly infected fruits is not essential for sporulation of M. fructigena .…”
Section: Discussionmentioning
confidence: 99%
“…The literature describes that fruit decay symptoms and signs on ripe peaches occur respectively within 48 h (Corbin and Cruickshank 1963;Ogawa et al 1995;Adaskaveg et al 2008) and 72 h (Hewitt and Leach 1939;Jenkins 1965;Sanoamuang and Gaunt 1995) after infection, but in some case those periods could vary (Biggs and Northover 1988;Sanoamuang and Gaunt 1995). In many pathosystems, variation in incubation and latent period are mainly caused by fruit injury (Corbin 1963;Xu and Robinson 2000a) and the effect of incubation temperature during spore production (Eversmeyer et al 1980;Bertolini and Tian 1997;Xu and Robinson 2000b).…”
Section: Discussionmentioning
confidence: 99%